m6A Methylation Regulator RBM15-Mediated Upregulation of ITGBL1 mRNA Stability Aggravates Colon Adenocarcinoma Progression by Remodeling the Tumor Microenvironment - Zhu, Jie; Liu, Dengliang; Zou, Yingying (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Colon adenocarcinoma (COAD) is a prevalent malignant tumor of the digestive system. Previous research has indi cated that RNA N6-methyladenosine (m6A) methyltransferase RNA-binding motif protein-15 (RBM15) is involved in various cancers. We aimed to investigate the function of RBM15 in COAD progression and its underlying molecular mechanism. Materials and Methods: TIMER and UALCAN databases were applied to analyze the relationship between COAD and Integrin !-like 1 protein (ITGBL1) or RBM15. RT-qPCR and Western blot were used to analyze ITGBL1, M2-type macrophage markers, EMT-related markers, and RBM15 expression. CCK-8, colony formation, and transwell experiments detected cell viability, proliferation, migration, and invasion. The effect of ITGBL1 on COAD tumor growth was examined using a xenograft tumor model. The effects of COAD cells on macrophage polarization and the proliferation and apoptosis of CD8+ T cells were analyzed using flow cytometry analysis. Relationships between RBM15 and ITGBL1 were validated using MeRIP and dual-luciferase reporter assay. Results: ITGBL1 and RBM15 contents were elevated in COAD. ITGBL1 knockdown could hinder COAD cell proliferation, migration, inva sion, M2-type macrophage polarization, and lymphocyte immunity. Meanwhile, the lack of RBM15 dampened tumor growth in vivo. Mechanistically, RBM15 could increase ITGBL1 expression by m6A methylation. Conclusion: RBM15 could promote COAD progression by regulating ITGBL1 mRNA stability, providing a promising biomarker and a potential target for COAD. Cite this article as: Zhu J, Liu D, Zou Y. M6A methylation regulator RBM15-mediated upregulation of ITGBL1 mRNA stability aggravates colon adenocarcinoma progression by remodeling the tumor microenvironment. Turk J Gastroenterol. 2025;36(6):343-356.